2002
DOI: 10.1200/jco.2002.09.045
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life of Long-Term Survivors of Non–Small-Cell Lung Cancer

Abstract: These findings provide the first description of the QOL of long-term survivors of lung cancer. Risk factors for poorer QOL are strongly linked to distressed mood, which is a potential target for intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
211
2
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(229 citation statements)
references
References 40 publications
(7 reference statements)
10
211
2
6
Order By: Relevance
“…Lung cancer survivors also showed close to a 6-fold increased likelihood for short sleep using fully adjusted model at a marginally significant level. The results are consistent with the previous studies reporting that lung cancer patients and survivors had the highest prevalence of sleep problems including insomnia (Davidson et al, 2002;Baker et al, 2005;Akyuz et al, 2013); and this can possibly be explained by comorbid conditions such as pulmonary diseases and respiratory distress components frequently reported among lung cancer survivors (Sarna and Brecht, 1997;Sarna et al, 2002).…”
Section: Discussionsupporting
confidence: 82%
“…Lung cancer survivors also showed close to a 6-fold increased likelihood for short sleep using fully adjusted model at a marginally significant level. The results are consistent with the previous studies reporting that lung cancer patients and survivors had the highest prevalence of sleep problems including insomnia (Davidson et al, 2002;Baker et al, 2005;Akyuz et al, 2013); and this can possibly be explained by comorbid conditions such as pulmonary diseases and respiratory distress components frequently reported among lung cancer survivors (Sarna and Brecht, 1997;Sarna et al, 2002).…”
Section: Discussionsupporting
confidence: 82%
“…69 -71 Research has shown that a significant proportion of Hodgkin disease survivors (22%), acute leukemia survivors (14 -31%), testicular cancer survivors (18%), long-term survivors of nonsmall cell lung cancer (22%), and breast cancer survivors (22-47%) report scores indicative of significant affective distress. 23,[72][73] A substantial proportion (33-54%) of BMT survivors experience significant psychological and emotional distress, such as mood disturbance, tension, and depression after completion of treatment. 16,18,74 High prevalence rates (45-65%) of anxiety and depression have been reported by breast cancer, BMT, colorectal, prostate, and lung cancer survivors.…”
Section: Group 2: Patients With Psychiatric And/or Psychological Sequmentioning
confidence: 99%
“…Support from a coresident may influence both the quality of life of cancer sufferers and their need for external services, including in-patient admission. Studies of particular patient groups from a range of settings have reported that cancer patients who live alone report more distress, poorer adjustment to diagnosis and have a poorer quality of life than those living with others (Forsberg and Cedermark, 1996;Akechi et al, 1998;Rustoen et al, 1999;Sollner et al, 1999;Sarna et al, 2002). Living arrangements may also influence chance of a home death, for which many people with cancer report a preference (Davison et al, 2001; Serra-Prat, Gallo and Picaza, 2001).…”
mentioning
confidence: 99%